Some microstructural studies of plasma-sprayed stainless steel 316L/Al2O3-TiO2 produced using two-powder port configuration - Phuangphaga Daram (2018)
This study concerns the development of a plasma spraying technique, in particular the 2-powder port setup which allows 2 different types of feedstock to be fed separately and sprayed at the same time resulting in the fabrication of a composite coating. The materials used to produce the composite coating are stainless steel 316L and Al 2 O 3 - TiO 2 . Stainless steel 316L can act as a binder and provide the coating with necessary toughness. Al 2 O 3 -TiO 2 is included to provide the coating with improved hardness. The contrast in the physical and thermal properties of the two materials poses some difficulties in plasma spraying. The resulted coatings were compared with those produced from pre-mixed powders (dry milling and wet milling) with respect to their microstructures, hardness and the deposition efficiency of the process. It was found that by adjusting the powder feed rates and the positions of the powder ports, composite coatings with good integrity can be fabricated. The hardness of the coating varies with the proportion of the Al 2 O 3 -TiO 2 phase, which in turn is affected by the powder feed rates. A coating containing approximately 70 vol.% Al 2 O 3 -TiO 2 having low porosity and moderate amount of unmelted particles with a hardness of 259 BHN and a relatively high deposition efficiency can be produced using a 2-port setup employing feed rates of 15 and 25 g/min. for Al 2 O 3 -TiO 2 and stainless steel 316L, respectively.